Seamless handover and QoS provisioning for mobile video applications in an integrated WiMAX/MIP/MPLS architecture. (25th September 2009) - Jailton Jr., Jose; Dias, Kelvin Lopes; Cerqueira, Eduardo; Cavalcanti, Dave
Mobility management with QoS (Quality of Service) support is a major requirement for the success of next generation wireless networks. With this goal in mind, this paper proposes a new architecture that integrates Mobile WiMAX (WorldWide Interoperability for Microwave Access) with MIP (Mobile IP) and MPLS (Multiprotocol Label Switching) protocols as well as a mobility prediction algorithm to enable seamless handover. The anticipated handover technique provides service continuity based on information about the MN's (Mobile Node) location and speed, as well as the BS's (Base Station) signal strength. The proposed architecture is also enhanced from the traffic engineering mechanisms provided by the MPLS protocol.